An Exergetic Performance Evaluation of Multiple Source Heat Pump Systems - Dikici, A.; Akbulut, A. (Taylor & Francis Inc, 2011)
In this study, some heat pumps having multiple heat source combinations were investigated experimentally. Multiple systems including mentioned heat pump systems, such as solar assisted-ground source, solar assisted-air source, and ground source-air source heat pumps, were tested. All the heat pump systems were designed and constructed in a test room with 60 m(2) floor area at Firat University, Elazig (38.41 degrees N, 39.14 degrees E), Turkey. In evaluating the efficiency of the heat pump systems, the most commonly used measure is the energy or the first law efficiency, which is modified to a coefficient of performance for heat pump systems. However, for indicating the possibilities for thermodynamic improvement, energy analysis inadequate and exergy analysis is needed. The coefficient of performance (COP) of solar assisted-ground source, solar assisted-air source, and ground-air source heat pumps as multiple source heat pump systems were also determined to be 3.36, 2.90, and 2.14, while the exergy losses of the refrigerant subsystems were approximately 2.13, 2.996, and 3.113 kW, respectively. Consequently. the energy and exergy loss analysis results show that the COP increases when the exergy loss of the condenser decreases. Exergetic performance coefficient is introduced and is applied to the heat pump systems having various heat sources. The results imply that the functional forms of the exergetic performance coefficient and first law efficiency are different. Results show that Ex(loss,total) becomes a minimum value where exergetic performance coefficient is the maximum value.
Keywords: energy analysis; exergy analysis; exergy efficiency; multiple source heat pump